(untitled) (Sciences & Technologie. B, Sciences de l’ingénieur, 2005)
A numerical model developed using the finite element Plaxis program is presented in this paper to simulate the behaviour of a stiff “L” shaped retaining wall supporting sand. For validating the proposed numerical model, reference was made to an experimental model tested in a centrifuge experiment. The proposed numerical model intended to predict the behaviour of a target prototype and to check the validity of the modelling concept used. Taking into account the geometry and dimensions of the wall with respect to the centrifuge scaling law, the loading conditions and considering the hardening soil model, it was found that the predicted pattern and magnitude of the wall displacements were close to the experimentally observed results. A good agreement between the measured and the numerically computed lateral pressures acting on the wall stem was also obtained with comparison to the classical approach.